Symmetry-preserving contact interaction model for heavy-light mesons - Serna, F. E. [UNESP]; Brito, M. A. [UNESP]; Krein, G. [UNESP]; Andrianov, A.; Brambilla, N.; Kim, V; Kolevatov, S. (Amer Inst Physics, 2016)
We use a symmetry-preserving regularization method of ultraviolet divergences in a vector-vector contact interaction model for low-energy QCD. The contact interaction is a representation of nonperturbative kernels used Dyson-Schwinger and Bethe-Salpeter equations. The regularization method is based on a subtraction scheme that avoids standard steps in the evaluation of divergent integrals that invariably lead to symmetry violation. Aiming at the study of heavy-light mesons, we have implemented the method to the pseudoscalar pi and K mesons. We have solved the Dyson-Schwinger equation for the u, d and s quark propagators, and obtained the bound-state Bethe-Salpeter amplitudes in a way that theWard-Green-Takahashi identities reflecting global symmetries of the model are satisfied for arbitrary routing of the momenta running in loop integrals.
Keywords: Regularization of ultraviolet divergences; Ward-Green-Takahashi identities; Dyson-Schwinger and Bethe-Salpeter equations